Two new cytotoxic and virucidal trisulfated triterpene glycosides from the antarctic sea cucumber Staurocucumis liouvillei - Maier, Marta Silvia (2001)
Two new trisulfated triterpene glycosides, liouvillosides A (1) and B (2), have been isolated from the Antarctic sea cucumber Staurocucumis liouvillei. Their structures have been elucidated by spectroscopic analysis (NMR and FABMS) and chemical transformations. Liouvillosides A (1) and B (2) are two new examples of a small number of trisulfated triterpene glycosides from sea cucumbers belonging to the family Cucumariidae. Both glycosides were found to be virucidal against herpes simplex virus type 1 (HSV-1) at concentrations below 10 μg/mL.